Obravnavanje gozdnih sestojev v gozdarskem načrtovanju na primeru gozdnih območij Bohinj in Pohorje - Poljanec, Aleš (Zbornik gozdarstva in lesarstva, 2006)
The research focused on the mapping, classifying and dealing with forest stands in forest management planning. Stands were analysed in the forest areasof Bohinj (Forest management region Bled) and Pohorje (FMR Maribor) with a total area of 29,95 0 hectares. Analyses of silvicultural units were carried out on a systematically selected sample, amounting to 9 % and 10 % of forest area at the Bohinj and Pohorje sites, respectively. The average area of delineated stands at the Bohinj site was 1.04 ha (Me = 0.5 3 ha) and 2.30 ha (Me = 1.33 ha) in the Pohorje site. The average area of silvicultural units is 2.00 ha (Me = 0.95 ha) at Bohinj and 1.88 ha (Me = 0.92 ha) at Pohorje sites. The size of stands depends mostly on stand structure, surveyor, site conditions, forest management practices and tradition.
Keywords: Bled; Bohinj; gospodarjenje z gozdovi; gozdna inventura; gozdni sestoji; gozdnogospodarski načrti